Early paleozoic evolution of the South Bainaimiao Ocean: constraints from the Chegendalai ophiolite mélange - Feng, Chenfei; Wang, Guosheng; Zhou, Zhiguang; Gao, Shen; Chen, Jianfeng; Hu, Hao (Frontiers in Earth Science, 2024)
IntroductionArc-continent collision contributes to the accretion of continental crust in the Central Asian Orogenic Belt. The Chegendalai ophiolitic mélange, located between the Bainaimiao arc and the North China Craton, is important to understanding the early Paleozoic evolution of the South Bainaimiao Ocean and arc-continent collision processes.MethodsIn this study, we provide Early Paleozoic geochronological and geochemical data from the Chegendalai ophiolitic mélange and island arc magmatic rocks in northern Damaoqi.ResultsZircon U-Pb dating of ultrabasic rocks and diabase porphyrite from the Chegendalai ophiolitic mélange yielded ages of 424 Ma and 431.9 Ma, respectively. Schist has an age of 421 Ma. Zircon U-Pb ages of island arc magmatic rocks are 425.7 Ma for tonalite, and 431 ± 11 Ma and 433.2 ± 4.4 Ma for granodiorite. Gabbro and ultrabasic rocks were formed in a volcanic arc basalt or mid-ocean ridge setting, displaying a tholeiitic basalt signature. These rocks likely derived from the lithospheric mantle with assimilation of crustal materials. Intermediate-acid magmatic rocks in northern Damaoqi are geochemically classified as I-type granites and exhibit characteristics of adakites.DiscussionThese rocks formed by partial melting of subducted plates and interactions with crustal and mantle wedges in a volcanic arc setting. Based on these results, we propose a three-stage evolution model for the South Bainaimiao Ocean: (i) Initial subduction during the Ordovician (∼450 Ma), where the Bainaimiao arc separated the South Bainaimiao Ocean from the PaleoAsian Ocean, with the former acting as a branch ocean basin of the latter; (ii) Northward subduction from the Ordovician to Late Silurian (450–424 Ma), with the South Bainaimiao Ocean subducting northward. The subducted slab partially melted and interacted with the crust-mantle wedge, leading to the formation of subduction-related island arc magmatic rocks; (iii) Closure during the Late Silurian (424–421 Ma), marked by the collision of the Bainaimiao arc with the North China Craton in an arc-continent collision, ending orogenesis with the Xibiehe Formation.